Psychoanalysis on the Civil-Military dictatorship (Research, Society and Development, 2022)
The civil-military dictatorship had been a rather obscure period of political, social and cultural repression during Brazil's brief history. The power centralized in a few power-holding representatives led a wave of violence in a legitimate way in favor of national security against the progressive ghost, even if this sacrificed the well-being of a good part of the population. Primarily based on the myth of the Father of the Horde, found in Freudian anthropology in Totem and Taboo (1913/1981), this article aims to discuss the genesis of authoritarianism that is claimed by the masses of the popular strata in the constitution of relations of political subordination between human beings, articulated with knowledge about the objects of jouissance, the infantile rupture with the parents and the consequent rejection of the truth in Lacan. As well as the theoretical developments proposed by his contemporary disciples in preventing the return of this form of politics.